(untitled) (Repertorio Científico, 2024)
Introduction: The teaching of chemistry has challenges due to students having difficulties in different topics. Therefore, it became necessary to develop new pedagogical strategies to improve student performance. This was most notable during the COVID-19 pandemic, where the need for different options where students could have access to real data-based laboratory experience to develop analytical and observational skills became apparent. A working group from the Universidad Estatal a Distancia de Costa Rica developed chemistry remote laboratories in 2020. A total of 63 613 uses have been registered in institutions from different countries, accessed through LabsLand. Objective: Systematise the usage statistics of ultra-concurrent remote chemistry laboratories in different educational contexts in order to determine the impact they have had on chemistry. Methods: We systematised the data available in LabsLand, such as the number of sessions, students and institutions over the last three years, and searched for articles focused on the use of these laboratories. Results: It was determined that Boyle’s law is the most used remote laboratory, there have been 6 publications on ultra-concurrent chemistry laboratories, remote laboratories have increased the internationalisation of different universities with the development of projects involving the participation of different countries. Conclusions: There is evidence of the impact of ultra-concurrent chemistry laboratories by the increase of uses after the pandemic. The work shows the interest of teachers in including these laboratories in their experimental activities. Collaboration with other countries increased the possibility of expanding the use of remote laboratories internationally